A COMMON FRAMEWORK FOR THEORIES OF NORM COMPLIANCE. Issue 1 (4th December 2018) - Morris, Adam; Cushman, Fiery
Abstract: Humans often comply with social norms, but the reasons why are disputed. Here, we unify a variety of influential explanations in a common decision framework, and identify the precise cognitive variables that norms might alter to induce compliance. Specifically, we situate current theories of norm compliance within the reinforcement learning framework, which is widely used to study value-guided learning and decision-making. This framework offers an appealingly precise language to distinguish between theories, highlights the various points of convergence and divergence, and suggests novel ways in which norms might penetrate our psychology.